Study on influencing factors of soil compaction effect of pipe pile in soft soil area - Zhang, Sifeng; Zhang, Xinyuan (Frontiers in Earth Science, 2025)
In recent years, prestressed pipe piles have been widely used in the reinforcement of soft soil foundation, and there will be obvious soil squeezing effect in the construction of pipe piles. However, the research on the soil squeezing effect of pipe piles under various influencing factors is not clear, and it is difficult to guide the actual construction on site. In this paper, the evolution mechanism of soil squeezing effect, pile-soil deformation characteristics and bearing characteristics in the process of pile sinking are analyzed in depth by means of field monitoring and laboratory test. Combined with visual model test, the distribution law of soil displacement field is clarified, and the effects of various influencing factors such as changing pile spacing and pile sinking sequence are revealed. The results show that the soil deformation caused by pile sinking increases first and then decreases in depth, and the soil deformation decreases exponentially in the horizontal direction. The width of the shear strain zone does not change with the increase of penetration, that is, the influence of the squeezing effect on the adjacent pile is mainly rotation and translation. For double piles, the expansion trend of the inner side of the two piles is smaller than that of the outer side of the pile. The squeezing effect will cause the adjacent pile to move and rotate. When the subsequent pile penetration is completed, the displacement field is no longer a basically symmetrical state, and the influence range in the depth area increases. When the pile spacing is set to more than 4 times the pile diameter, the synergistic bearing capacity of the pile group can be better played; The construction sequence from near to far is preferentially selected during construction, which can effectively reduce the impact on adjacent structures. The research results of this paper can provide a reference for further solving the disposal problem of composite foundation reinforced by pipe pile group.